Association of Work-Related Risk Factors and Lateral Epicondylitis among Chefs in Lahore - Mehak Matloob, Tayyaba Fatima, Nageen Baig, Sadia Khalid, Hamail Irfan, Adnan Hashim, Muhammad Shamshad Tabassum (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most common type of myotendinosis is lateral epicondylitis, which causes significant pain and loss of function in the affected limb. The peculiarities of muscular biomechanics and equipment are significant in preventing the disorders. It was a painful condition that injured the tendinous tissue of the lateral epicondyle of the humerus, prompting amputation of the limb. Methods: A cross sectional study was conducted in Lahore. The data was collected from Chef, working in different restaurants. The questionnaire used in this study was Patient-Rated Tennis Elbow Evaluation (PRTEE). Consent form and questionnaire were given to the participants. Independent T-test was applied. The data was evaluated by using the SPSS version 25. Results: Results analyzed by SPSS. Sample size of population was 136. Statistics for gender, maximum were males (78.7%) and Females (21.3%), while 64.7% were Right-Handed 35.3% were Left-Hand. Minimum age was 25 years and Maximum age was 50 years. Conclusion: Hence, it was concluded that chefs had pain in their left or right hand (more on dominant right hand) on lateral side due to different factors. It was also concluded that there is association between male and female during work related activities. Keywords: Lateral Epicondylitis, Myotendinosis, Patient-Rated Tennis Elbow Evaluation (PRTEE)